A FLEXIBILIZAÇÃO DAS RELAÇÕES DE TRABALHO E SUAS IMPLICAÇÕES NA PRÁTICA PEDAGÓGICA: os estagiários da educação infantil na rede de ensino de Guarapuava/PR - GUARAGNI, MARIANA PRADO (2016)
The objective of this research is to analysis work relations, students/trainees’ labor conditions in Children’s Education who works in learning institutions in Guarapuava-PR and the influence of these factors in their pedagogical practice. It is understood that the remunerated traineeship is on the threshold of educational sphere as well as labor. It brings in its essence a certain clash of perspectives, since ithas educational and labor dimensions and its current model as a flexible labor activity and it can undermine in certain way students/trainees’ pedagogical practices. In other words, a kind of activity that is a flexible work – flexibility to hire and to dismiss, flexibility of salaries, work hours, functions etc and it is precarious, since there are not labor rights and social security. Based on this assumption, it was decided to carry out analyses of qualitative and quantitative data that were collected by interviews and questionnaires applied to twenty-two Children Education student/trainees. Therefore, to interpret and comprehend the object of this study it was chosen as guide the theoretical and methodological assumptions of Marx’s social theory. From the presented and discussed empiric information the conclusion was, in fact, that the remunerated traineeship is a flexible, precarious, intense and exploratory activity which impacts negatively students’ pedagogical practices, consisting in a formative activity with small relation with the theoretical assumptions learnt at the university, since activities are presented as fragmentary androutine activities. Besides, it was identified that the traineeship provides tacit knowledge that comes from daily experiences and it does not contributes to praxical activity which is important to compose the teacher’s professional formation.